Normativité des modèles et régimes du futur - Fabrizio Li Vigni (Revue d'anthropologie des connaissances)
On the basis of a sociological study of two specialties – quantitative geography and computational epidemiology – inscribed in “complex systems sciences”, the article questions the alleged unity of this multidisciplinary and transnational domain, often presented in the singular under the expression of “complexity science”. Whatever the take is – historical origins, research practices, epistemologies or institutions – complexity sciences appear in all their social and epistemic diversity. If these aspects have been weakly treated by human and social sciences literature, their normative viewpoints and their transepistemic activities have not been the subject of any systematic study. Thanks to the concept of “anticipation community” proposed by sociologist Céline Granjou, which permits to keep together at the same time a mode of knowledge production, a certain type of transepistemic activities, a certain relationship to the future and a certain normative viewpoint about the world, the analysis offers the description of three groups – called “the community of the urbanistic counseling” (geography), the “community of epidemiological decision aid” (epidemiology) and the “community of socio-ecological companion modeling” (geography and other disciplines). The article contributes thus to deconstruct the unitary image of complexity sciences, which some of its representatives and observers contribute to entertain, and offers a possible application of the concept of “anticipation community”, discussed and adapted here to the study object of this article.